DEVELOPMENT OF A CREATIVE DESIGN TRAINING MODEL IN PLAYGROUP TEACHERS IN SEMARANG CITY - Kamsidjo Budi Utomo (Universal Institute of Professional Management, 2020)
The purpose of this study is to produce an effective training model and the formation of Playgroup teachers who have better creative drawing competence than before. This research approach is a research and development (R&D) design. These stages, namely the collection of data needs for model development, design development of model development, model validation of model trials (individual, group, and limited), model revisions, model trials, and final model revisions. The results of this study are creative drawing training models that have proven their effectiveness. The results of the effectiveness test showed a pretest value, namely a B value (10%), a C value (15%), and a D value (75%). The posttest results showed that the value of A (60%), and the value of B (40%). The results of the study concluded that the final model of development results was effective and could develop creative drawing competencies in Playgroup teachers. The development research model is recommended to be recommended as a model / pilot project in Semarang City.